Brewing up a business : adventures in beer from the founder of Dogfish Head Craft Brewery - Calagione, Sam. 1969- (Hoboken, N.J. : Wiley, 2011)
"Updated business wisdom from the founder of Dogfish Head, the nation's fastest growing independent craft brewery Starting with nothing more than a home brewing kit, Sam Calagione turned his entrepreneurial dream into a foamy reality in the form of Dogfish Head Craft Brewery, one of America's best and fastest growing craft breweries. In this newly updated Second Edition, Calagione offers a deeper real-world look at entrepreneurship and what it takes to operate and grow a successful business. In several new chapters, he discusses Dogfish's most innovative marketing ideas, including how social media has become an integral part of the business model and how other small businesses can use it to catch up with bigger competitors. Calagione also presents a compelling argument for choosing to keep his business small and artisanal, despite growing demand for his products. Updated to offer a more complete look at what it takes to keep a small business booming An inspiring story of renegade entrepreneurialism and the rewards of dreaming big, working hard, and thinking unconventionally Shows how to use social media to reach new customers and grow a business For any entrepreneur with a dream, Brewing Up a Business, Second Edition presents an enlightening, in-depth look at what it takes to succeed on their own terms."--Provided by publisher.
Foreword: The Passion Of The Individual. -- Preface. -- Introduction. -- Chapter 1 The Unconventional Beginnings Of An Entrepreneur. -- Chapter 2 Business From The Inside Out. -- Chapter 3 Keeping Your Balance. -- Chapter 4 Creating A Business Offering. -- Chapter 5 Crafting A Brand In A Cookie-Cutter World. -- Chapter 6 Marketing On A Small -- Business Budget. -- Chapter 7 Publicity Stunts (Are Poorly Named). -- Chapter 8 Stalking The Killer App. -- Chapter 9 Selling Distinction, Specialization, And Variety. -- Chapter 10 Cash Is King (Well, Sort Of). -- Chapter 11 Leadership. -- Chapter 12 Effectively Managing Coworkers. -- Chapter 13 Working Toward Irrelevance. -- Chapter 14 To Small-Business Success.
Includes index.
Keywords: Dogfish Head Craft Brewery; Microbreweries -- Delaware; Entrepreneurship -- Delaware; Small business -- Delaware